Development, Characterization, and In-Vitro Antimicrobial Activity of Lawsonia inermis L. Leaves Hydro-Alcoholic Extract-Based Vaginal Suppositories - Fakeha Firdous K; Khaleequr Rahman; Arshiya Sultana; Shamsiya Khan (Tehran University of Medical Sciences, 2023)
Lawsonia inermis (henna) leaves have good antimicrobial, anti-inflammatory and wound healing properties. It is used topically in the form of hamul in gynaecological infections in traditional medicine. However, due to the unpleasant dosage form, it has very low patient compliance. Hence, in this study hydro-alcoholic extract-based vaginal suppository of henna leaves was formulated and evaluated for various parameters. Multiple batches of suppository were prepared using polyethylene glycol (PEG)-4000, PEG-400, Tween-80, Span-60, distilled water and hydro-alcoholic extract. Based on the organoleptic character and optimization tests, the final batch was selected. The final batch was evaluated for various physicochemical parameters and antimicrobial activities. Batch containing extract 30%, PEG-4000 37.38%, PEG-400 19%, distilled water 4.55%, Tween-80 and Span 60 4.535% each, passed the disintegration time (11.45mnts), muco-adhesiveness (90°) and melting point (37°C) test and selected as an optimized batch. The mean weight of a suppository was 1.56±0.03g. Secondary plant metabolites in henna leaves and suppository were comparable. Various molecules identified in leaves were also noted in the suppository on GCMS. Heavy metals and microbial contamination were within the permissible limit. Zone of inhibition (at 50µg/ml) and minimum inhibitory concentration for E. coli, S. aureus, S. pyogenes, P. aeruginosa and C. albicans were 20mm, 18mm, 20mm, 16mm, 19mm and 20µg/ml, 10µg/ml, 25µg/ml, 25µg/ml, 45µg/ml respectively. This study indicated satisfactory physicochemical parameters and antimicrobial potential of the hydro-alcoholic extract-based vaginal suppository of henna. Hence, it may be considered as a better alternative to its traditional dosage form.